Relasi UMKM, Pemerintah Daerah, dan Sektor Perbankan dalam Implementasi Kebijakan Pengembangan Ekonomi di Era Pandemi Covid-19 - Loveita Eka Sari; Kgs. M. Sobri; Andries Lionardo; Abdul Nadjib (Universitas Medan Area, 2022)
This study attempts to evaluate the extent of the relationship between small, micro and medium enterprises (MSMEs) and the banking sector in executing economic development strategies in the Covid-19 epidemic era. A qualitative method using a case study approach is utilized to see the link between MSMEs and the banking sector in this study. The research was done in Palembang City with informants from Rural Banks (BPR), Palembang City Government, and MSME actors who issued loans to BPRs. This study indicates that there is a good interaction between BPR, Palembang City Government, and MSME actors in executing economic development strategies in the era of the Covid-19 pandemic. The assistance given by BPR and the City Government can allow MSMEs to tackle numerous challenges in the middle of a pandemic. Previous study has not often explored the interaction between the three stakeholders (MSMEs, Regional Governments, and the Banking Sector) in economic recovery in the age of the Covid-19 epidemic. Whereas the support offered to MSMEs might stimulate economic activity in a region.